Pengaruh Lokasi dan Promosi Terhadap Keputusan Pembelian pada Mie Jaya Bintaro Tangerang Selatan - Ade Rachmawan; Raden Roro Ayu Metarini; Sunanto Sunanto (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
In the competitive culinary industry, purchasing decisions are influenced by various factors including location convenience and promotional activities. Mie Jaya Bintaro, South Tangerang, faces intense competition, making it important to understand determinants of consumer purchasing decisions. This study aims to determine the effect of location and promotion on purchasing decisions at Mie Jaya Bintaro, both partially and simultaneously. The research employed a quantitative approach. The population consisted of 28,780 consumers, with a sample of 100 respondents selected using the Slovin formula and simple random sampling technique. Primary data were collected through questionnaires using a Likert scale. The data were analyzed using SPSS version 27 and multiple linear regression analysis. The results indicate that both location and promotion have a significant positive effect on purchasing decisions, either partially or simultaneously. This implies that strategic location accessibility and effective promotional activities play an important role in attracting consumers and increasing purchasing decisions at Mie Jaya Bintaro. Therefore, improving these aspects can enhance customer engagement and business performance. These findings suggest that business managers should prioritize both location strategy and promotional effectiveness to increase consumer purchase intention and sustain competitiveness in the local food market for sustainable growth in competitive culinary industry context specifically.